Production of thermochromic microcapsulated inks for smart packaging and examination of printability properties - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2020)
Purpose Stimulant-sensitive materials exhibit physical or chemical reversible changes in their properties as a result of environmental variables. One of these materials is thermochromic materials. Materials with thermochromic sensitivity change their color with heat exchange. For this reason, it can be used in many different fields such as security inks. Such substances decompose rapidly by being affected by weather conditions. Furthermore, the particle sizes are larger than normal pigments, and therefore, it is difficult to stabilize thermochromic dyes. Because of all these adverse conditions, thermochromic colorants must be protected before use in the ink. This protection is planned to be provided by the microcapsulation technique. The purpose of this study is to determine the thermochromic printing inks that can be stored stably by microcapsulation technique, to protect it from environmental conditions and the determination of printability parameters. Design/methodology/approach In this study, capsules with a core material of thermochromic dyeing with polyurea formaldehyde (PUF) or poly-phenolmelamine formaldehyde (PMF) shell were synthesized at appropriate pH and temperature using the appropriate solvent and mixing speed. The chemical structure and dimensions of the obtained capsules were examined by ATR-FTIR and scanning electron microscopy, respectively. The produced thermochromic microcapsules were mixed with alkyd resin and mineral oil and screen printing ink was obtained. Printability tests such as surface morphology, color, gloss and light fastness were applied. Findings As a result, it was determined that PMF is not a suitable encapsulation technique for thermochromic dyes under suitable conditions and eliminates thermochromic property by providing heat stability. It was found that PUF microcapsulation can be used in thermochromic dyestuff encapsulation and does not lose the thermochromic property. It has also been found that PUF microcapsules increase the lightfastness and stability of thermochromic dye ink. Originality/value This study provides experimental research on the encapsulation of a thermochromic dye and its use in ink.
Keywords: Lightfastness; Microcapsulation; Printability; Safety ink; Thermochromic ink; PHENOL-FORMALDEHYDE MICROCAPSULES; EPOXY; RESINS